2020
DOI: 10.3389/fspor.2020.570449
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Human Ankle Stiffness During Standing Balance

Abstract: The purpose of this study is to quantify sex differences in 2-dimensional (2D) ankle stiffness during upright standing balance and investigate the mechanisms for the differences. A dual-axis robotic platform, capable of perturbing the ankle and measuring the corresponding ankle torques in both the sagittal and frontal planes, was used to reliably quantify the 2D ankle stiffness while healthy young human subjects perform a range of standing balance tasks, specifically, ankle muscle co-contraction tasks, weight-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
(46 reference statements)
4
4
0
Order By: Relevance
“…This greater contribution of the ankle muscles could be adopted by females to counterbalance anatomical and mechanical differences (i.e. lower ankle stiffness for females) between the sexes, as previously demonstrated in the literature 25 . However, the observed neuromuscular difference between males and females did not generate an interaction with fatigue.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This greater contribution of the ankle muscles could be adopted by females to counterbalance anatomical and mechanical differences (i.e. lower ankle stiffness for females) between the sexes, as previously demonstrated in the literature 25 . However, the observed neuromuscular difference between males and females did not generate an interaction with fatigue.…”
Section: Discussionsupporting
confidence: 60%
“…lower ankle stiffness for females) between the sexes, as previously demonstrated in the literature. 25 However, the observed neuromuscular difference between males and females did not generate an interaction with fatigue.…”
Section: Discussionmentioning
confidence: 85%
“…Regarding the ankle, previous studies have demonstrated sex-related differences in anatomical and biomechanical features of the joint [ 59 ]. Adjei, Nalam, & Lee [ 66 ], congruently with Trevino and Lee [ 67 ], found that ankle stiffness varied significantly between sexes, both along the sagittal and frontal planes (therefore concurring in dorsiflexion/plantarflexion and inversion/eversion, respectively), with greater joint stiffness in females while both quiet standing and muscle activation occurred. The authors explain their findings with the greater passive resistance of females to a greater range of motion, lower elastic modulus, and higher ligamentous laxity [ 68 , 69 , 70 ] than males, which by contrast possess more leg muscle mass [ 71 ] and a higher muscle and cortical bone cross-sectional area in the whole lower limb [ 7 , 9 , 72 ] than females.…”
Section: Discussionmentioning
confidence: 86%
“…Six able-bodied young participants were recruited to perform a series of experiments to validate the overall efficacy of the SR-AFO. The first performance evaluation was conducted using a dual-axis robotic platform, which characterized ankle stiffness as done in previous works with the participant staying in a quiet standing position ( Nalam et al, 2020 ; Adjei et al, 2020 ). The MAVS actuators were evaluated using the platform with the SR-AFO donned on the right foot in three conditions: passive (no pressure) and two pressure levels.…”
Section: Discussionmentioning
confidence: 99%
“…The dual-axis robotic platform (Figure 12a), capable of applying position perturbations to the ankle in the sagittal and frontal planes and measuring the corresponding ankle torques, was used to quantify 2D ankle stiffness in both the sagittal and frontal planes. The platform was validated to accurately quantify 2D ankle stiffness during upright standing (Nalam and Lee, 2018; Nalam and Lee, 2019; Adjei et al, 2020; Nalam et al, 2020). The subject was asked to stand with the right foot placed on the robotic platform and the left foot on the elevated ground right next to the platform.…”
Section: Human Trials and Experimental Evaluation Of The Sr-afomentioning
confidence: 99%